Quality Improvement Management at MTSN 1 Ogan Komer-ing Ilir (Lembaga Pengembangan Kinerja Dosen, 2025)
Improving the quality of education is a strategic demand in responding to global dynamics and community demands for the quality of educational institutions, including madrasahs. MTsN 1 Ogan Komering Ilir as one of the formal Islamic educational institutions strives to build a structured quality management system to improve the academic quality and character of students. This study aims to analyze the implementation strategy of quality improvement management at MTsN 1 Ogan Komering Ilir, identify the obstacles faced, and explore strategic opportunities that can be utilized in the quality improvement process. This study uses a descriptive qualitative method with a case study approach, and data were collected through observation, documentation studies, and in-depth interviews with four main informants. The results of the study indicate that madrasahs have implemented quality management strategies through data-based planning, implementation of teacher capacity building programs, strengthening learning, and periodic quality evaluations. However, there are still obstacles such as limited human resources, lack of quality literacy, and limited use of information technology. On the other hand, there are opportunities such as support from national policies, commitment from madrasah leaders, and stakeholder participation that can be maximized to strengthen the quality system in a sustainable manner.